PELATIHAN SOAL MATEMATIKA BERBASIS METODE DRILL PADA SISWA SMP NEGERI KOTA BARU KEFAMENANU NUSA TENGGARA TIMUR - Ahsan, Zulkaidah Nur; Siahaan, Meiva Marthaulina Lestari; Handayani, Rika; Fitriani, Fitriani; Laja, Yosepha Patricia Wua (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
The outcomes of situation analysis in SMP Negeri Kota Baru Kefamenanu East of Nusa Tenggara is the low achievement of students' mathematics learning outcomes seen from the evaluation results of mathematics subjects in the last four semesters and low learning motivation based on the results of teacher interviews. Therefore, we need an activity that aims to conduct training on math problems for grade 9 students and increase student motivation in learning mathematics. The drill method is a method for giving problems repeatedly. This method is considered relevant to the purpose of community service activities. The stages of community service activities begin with giving a pre-test, giving training on math questions, giving a post-test, and ending with giving a questionnaire regarding student motivation. The result of the community service activity was that there was an increase in students' understanding in working on math problems seen from a comparison of the results of the pre-test (29.05%) and post-test (94.76%) and students were increasingly motivated in learning mathematics refer to the results of the questionnaire. Based on the evidence, it’s crystal clear that service community activity is useful for training students to solve non-routine math problem and motivating students to learn mathematics.